Assessing pilgrims' disposition to Islamic insurance during Hajj / Faezah Abdul Majeed Shafei - Abdul Majeed Shafei, Faezah (2015)
Hajj is an annual ritual that requires a pilgrimage to go to Makkah. There are two authorities cooperating with one another to ensure that the pilgrims' intention to perform the Hajj is fulfilled. They are, the Ministry of Hajj and Hajj Agencies based in Makkah. The duration for the activities involved in this religious obligation is approximately three months. Within this period, pilgrims are exposed to all kinds of potential risks, ranging from personal risks, risks incurred during the travel from the pilgrim's homeland to Makkah, risks during the performance of Hajj itself and the exposure of risks after its completion. This research is undertaken to investigate risks faced by the pilgrims during the Hajj period in an attempt to provide better understanding about Islamic insurance coverage among the pilgrims. This study is also attempted to investigate how Islamic insurance product is necessary for providing pilgrims with financial security by identifying the demand for the coverage. At the same time, the study conducted is also to ensure the relevant parties involved would also contribute towards the pilgrims' welfare.